Influence of Colonies’ Morphological Cues on Cellular Uptake Capacity of Nanoparticles - Huang, Siyuan; Su, Qi; Hou, Xiaoqiang; Han, Kuankuan; Ma, Shufang; Xu, Bingshe; Yang, Yingjun (Frontiers in Bioengineering and Biotechnology, 2022)
High transmembrane delivery efficiency of nanoparticles has attracted substantial interest for biomedical applications. It has been proved that the desired physicochemical properties of nanoparticles were efficient for obtaining a high cellular uptake capacity. On the other hand, biophysical stimuli from in situ microenvironment were also indicated as another essential factor in the regulation of cellular uptake capacity. Unfortunately, the influence of colony morphology on cellular uptake capacity was rarely analyzed. In this study, micropatterned PDMS stencils containing circular holes of 800/1,200 μm in diameter were applied to control colonies’ size. The amino-modified nanoparticles were cocultured with micropatterned colonies to analyze the influence of colonies’ morphology on the cellular uptake capacity of nanoparticles. Consequently, more endocytosed nanoparticles in larger colonies were related with a bigger dose of nanoparticles within a larger area. Additionally, the high cell density decreased the membrane–nanoparticles’ contacting probability but enhanced clathrin-mediated endocytosis. With these contrary effects, the cells with medium cell density or located in the peripheral region of the micropatterned colonies showed a higher cellular uptake capacity of nanoparticles.